Increasing Understanding of Financial Literacy for Generation Z in Palembang City - Desri Yanto (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
Understanding of financial literacy in Indonesia is still low. Likewise, regarding the level of financial literacy in the city of Palembang, the people of Palembang city are still few who have financial literacy, especially Generation Z. Lack of understanding related to financial literacy for Generation Z in the city of Palembang, the implementation of community service related to increasing understanding of financial literacy is needed by Generation Z. Z city of Palembang. The implementation of this activity is carried out by providing material related to financial literacy online using the Zoom Metting application. This service activity can increase Generation Z's understanding of financial literacy.